Screening and characterisation of wine related enzymes produced by wine associated lactic acid bacteria - Mtshali, Phillip Senzo (Stellenbosch : University of Stellenbosch, 2008)
Thesis (Msc (Viticulture and Oenology))--University of Stellenbosch, 2007.